Sexual dimorphism in the shell of a nassariid gastropod. A 3D geometric morphometrics approach - Marquez, Federico (2017)
Among gastropods, dimorphism is reported in shell size, radular characteristic, and to a lesser extent in shell shape. The relationship of dimorphic characters of the shell with spawning is scarcely studied in literature. Buccinanops globulosus is an interesting model to study sexual dimorphism in shell shape, because the adults attach their egg capsules to the females' own shells (callus zone). Our hypothesis is that the shell dimorphism is evidenced in the form (size and shape) of callus zones of the females' shells, compared with the males'. In order to test this hypothesis we use a 3D geometric morphometrics (GM) method with several advantages over 2D GM. The relationship between callus shape and size was allometric. During growth, the main callus shape changes are related to the mean size increment, which is more evident in larger females. These callus zones are characteristically slender in males and small females, and more inflated in large females. Our analyses revealed that female shells are different from male ones and those differences are significant on the callus zone where the egg capsules are attached by the female. This finding suggests a relationship of the shell form with spawning. Our findings are not only relevant in terms of the shell dimorphism of the particular spawning substrate area (callus zones) and its reproductive implications, but also provide insights into the evaluation of shell shape variation on areas without type I or II anatomical landmarks in 3D GM.